Wide vector solitons in systems with time- and space-modulated nonlinearities - Arroyo Meza, L. E. [UNESP]; Souza Dutra, A. de [UNESP]; Hott, M. B. [UNESP] (Amer Physical Soc, 2013)
In this work we apply point canonical transformations to solve some classes of two coupled nonautonomous nonlinear Schrodinger equations with specific cubic and quintic-time- and space-dependent-nonlinearities. The method applied here allows us to find a class of wide localized (in space) vector soliton solutions of nonautonomous nonlinear Schrodinger equations. The vector solitons found here can be applied to theoretical studies of Bose-condensed atoms in two different internal states and of ultrashort pulse propagation in optical fibers with focusing and defocusing nonlinearities.